Metastasis of breast cancer in myometrium, detected exclusively through 18F-FDG PET/CT : interesting images - Hsiao, Yeong-Shin; Shen, Shu-Chane; Hsiao, Shih-Chuan (Clinical nuclear medicine, 2025)
We share the case of a 50-year-old woman with isolated myometrial metastasis of recurrent invasive breast ductal carcinoma. Eight years after initial diagnosis at stage IIIC, a hypodense myometrial tumor was spotted in whole-body CT, which was also noted as a lesion with high SUV in 18F-FDG PET/CT. Myometrial metastatic mammary carcinoma was then pathologically proven after hysterectomy and bilateral oophorectomy. This case warns us to be alert to how easily malignant uterine lesions could be misjudged as benign in traditional imaging and, consequently, how irreplaceable PET/CT is in the early diagnosis and treatment of malignant diseases.